Cassava intake and vitamin A status among women and preschool children in Akwa-Ibom, Nigeria - Moura, Fabiana F. de; Moursi, M.; Lubowa, A.; Ha, B.; Boy, Erick; Oguntona, B.; Maziya-Dixon, B.B. (Public Library of Science, 2015)
Background: As part of the HarvestPlus provitamin A-biofortified cassava program in Nigeria we conducted a survey to determine the cassava intake and prevalence of vitamin A deficiency among children 6-59 months and women of childbearing age in the state of Akwa Ibom.